Design analysis of single layer coupled coils - Yunas, Jumril; Sulaiman, Nadzril; Bahadorimehr, Ali R.; Yeop Majlis, Burhanuddin (2010)
This paper presents an analysis on the design of coupled coil. The coil platform that has been developed is a single layer coil structure on the planar surface of the substrate. the structure offers an integrated solution for customizable application due to its compact and small size. The design of the spiral coil has been analysed using field solver analysis ASITIC. As a demonstration of the usefulness of such analysis, a coupled coil is fabricated on a glass substrate and measured at frequency range between 50 MHz and 800 MHz. A coupling factor of about 0.7 and self inductance of 12.7 nH were achieved which show a good agreement with the simulation.